Effectiveness of influenza vaccination in the elderly: a population-based case-crossover study. Issue 2 (21st February 2022) - Liang, Chun-Yu; Hwang, Shinn-Jang; Lin, Kuan-Chia; Li, Chung-Yi; Loh, Ching-Hui; Chan, James Yi-Hsin; Wang, Kwua-Yun
Abstract : Background: There is limited information regarding the effectiveness of influenza vaccines for older adults. Particularly, controlling for healthy senior bias is challenging in observational studies. We aimed to assess the efficacy of influenza vaccination in the elderly while addressing potential healthy senior bias and whether it was related to virus-vaccine strains matching. Method: To control between-individual confounder, we used a case-crossover study design using Taiwan's National Health Insurance Research Dataset to analyse the association between influenza vaccination in older adults and the risk of hospitalisation for community-acquired pneumonia (CAP). Individuals were a 'case' in vaccinated years and a 'control' in unvaccinated years. The study periods were 2006/2007 and 2007/2008 seasons because virus-vaccine strains were matching in 2006/2007 season and unmatching in 2007/2008 season. Older adults were categorised into two groups: admitted for CAP during the pre-vaccination period (Admitted, n=311) and not hospital admitted for CAP (Non-admitted, n=572 432). The outcome was hospitalisation for CAP during the influenza period. Conditional logistic regression assessed influenza vaccine efficacy in reducing CAP. Results: Influenza vaccination had no protective effects in Admitted group. However, because of the tiny numbers in Admitted group, we could draw very limited conclusions. Receiving an influenza vaccine significantly prevented CAP in Non-admitted group only during the vaccine-circulating strain-matched year (OR, 0.72; 95% CI, 0.64 to 0.83). In addition, there was no protective effect against CAP hospitalisation among individuals with a Charlson Comorbidity Index score over 2. Conclusion: Influenza vaccine efficacy was associated with vaccine-circulating strain-matched. When vaccine-circulating strains were all matching, receiving a shot reduced the probability of CAP hospitalisation by 28% in Non-admitted group. However, high comorbidity may reduce the vaccine efficacy. Therefore, it is necessary to educate older adults to receive annual influenza vaccination and in combination with non-pharmaceutical interventions to reduce the risk of CAP.